Physiological characteristics underpinning successful cryopreservation of endemic and endangered species of Bromeliaceae from the Brazilian Atlantic Forest. (12th November 2014) - Rodrigues, Alba R. P.; Forzza, Rafaela C.; Andrade, Antonio C. S.
<x xml:space="preserve">Abstract</x> The germination requirements and the basis of the optimal water content before and after cryopreservation were studied for ten endangered Brazilian species of Bromeliaceae. Constant and alternating temperature regimes were used to determine the best conditions for seed germination. The relationship between seed water content and relative humidity was evaluated using water sorption isotherms at 15 °C. Seeds were cryostored at four water contents (3, 5, 7 and 9%) and three storage periods (0, 180 and 365 days), and loss in viability and vigour were estimated. Fresh seeds of all species showed maximum germination in < 30 days at temperatures between 20 and 30 °C, indicating the absence of a physical/morphological dormancy. A sigmoidal relationship between seed water content and relative humidity was observed with no apparent differences in sorption characteristics among the species. The optimum water content for cryopreservation of most of these species was c. 7%. Ultra‐drying (3% seed water content) had a detrimental effect on seed viability and vigour. Our experiments suggested orthodox storage behaviour for all species of Bromeliaceae examined as they are able to survive desiccation and freezing. This study has shown the feasibility of ex situ conservation in seed cryobanks of endangered bromeliads from the Brazilian Atlantic Forest to support future reintroduction of these species in nature. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 176, 567–576.